Treatment of recurrent priapism using proximal shunt: Quackles technique - Miguel Toledo Jiménez; David Carracedo Calvo; Pietro Moscatiello; Alessandro Fiorillo; Rebeca Quintana Álvarez; Nathalie Pereira Rodríguez; Irene Hernández Bermejo; Iñigo Miñana Toscano; Miguel Sánchez Encinas (IJU Case Reports)
Introduction Recurrent priapism is a rare variant of ischemic priapism that involves recurrent erections typically lasting less than 4 h. The primary goal of treatment is to prevent future episodes, with options ranging from pharmacological treatments to various surgeries. Case presentation A 38‐year‐old man experienced multiple episodes of priapism that were refractory to angioembolization of an arteriocavernous fistula and oral treatment with Cetirizine and Bicalutamide. After the patient refused intracavernous self‐injections, various surgical options were considered. Ultimately, a proximal penile shunt surgery with a cavernosal–spongiosal shunt using the Quackles technique was chosen, which proved effective in preventing episodes and did not affect the patient's erectile function. Conclusion Penile shunt surgery using the Quackles proximal technique is a safe and effective option for the treatment of recurrent priapism.